Ochratoxin A in roasted coffee commercially sold in the city of Rio de Janeiro - Marco Antonio Mota; Vanessa Elen de França Valle; Maria HeloÃsa Paulino Moraes; Elaine Santos Lima (Fundação Oswaldo Cruz (FIOCRUZ), 2015)
The objective of this study was to evaluate the incidence of ochratoxin A (OTA) in roasted and ground coffee commercially sold in Rio de Janeiro in 2002â€"2003 and 2012â€"2013. Samples were prepared using an immunoaffinity column, and OTA was quantified by HPLC using a fluorescence detector (LOD of 0.3 ÂµgÂ·kgâˆ'1 and LOQ of 0.7 ÂµgÂ·kgâˆ'1). In total, 29 samples were collected in 2002â€"2003, with 12 samples containing levels below the LOD and 17 samples containing levels in the range of 0.3â€"5.7 ÂµgÂ·kgâˆ'1. In the monitoring conducted in 2012â€"2013, 37 samples were evaluated, with only 02 samples having levels below LOD. The remaining 35 samples had levels in the range of 0.3â€"3.1 ÂµgÂ·kgâˆ'1. OTA concentrations in all samples were lower than the maximum tolerable limit set by the Brazilian legislation (10 ÂµgÂ·kgâˆ'1). However, it is relevant to stress the importance of OTA control in coffee as a product consumed daily by Brazilians.